Ordered Heme Binding Ensures the Assembly of Fully Functional Hemoglobin: A Hypothesis - Vasudevan, G.; McDonald, M.J. (Current Protein and Peptide Science, 2002)
The exact mechanism by which four Fe-Protoporphyrin-IX (heme) moieties and four nascent globin chains combine to form human hemoglobin (α2β2) remains a mystery. Recent Soret spectral static and kinetic studies of the incorporation of CN-Hemin derivatives into an array of human globin species have provided in vitro evidence of an ordered assembly pathway, through an αheme-βglobin intermediate, that ensures correct formation of active hemoglobin tetramers.
Keywords: Fe-Protoporphyrin-IX